Hip Arthroplasty Following Subtotal Sacrectomy for Chordoma - CLAXTON, MATTHEW R. (In Vivo, 2020)
Background/Aim: Chordomas often affect the sacrum with a high predilection for local-regional recurrence. Patients typically retain their ability to ambulate, and the development of metastatic disease in the periacetabular region can have significant morbidity and pain with ambulation. The purpose of the study was to describe the outcome of patients undergoing a hip arthroplasty following resection of a sacral chordoma. Patients and Methods: From 1990 to 2015, 84 patients underwent sacrectomy for chordoma, while four of these (5%) patients underwent hip arthroplasty. The most common level of nerve root sacrifice was S2-5 (n=2). The mean time between sacrectomy and hip arthroplasty was 7 years. Indications for arthroplasty included metastatic disease (n=3) and coxarthrosis (n=1). Results: Postoperatively two patients ambulated with a gait aid, and no patient had a Trendelenburg gait. The mean Harris Hip Score significantly improved from 49 to 80 postoperatively (p=0.02). Conclusion: The results of this study indicate that hip arthroplasty is a durable treatment option for patients with metastatic disease or coxarthrosis following subtotal sacrectomy for chordoma.